Segurança contra incêndio em edifício habitacional de baixo custo estruturado em aço - Karina Venancio Bonitese (2007)
The evacuation process of a building is associated with its architectural features but also with the physics and psychological factors of the population in a panic situation. Thus, it is necessary to study the consequences of a fire situation for the building, since the lives of the occupants who are in the building must be protected, included the firefighters. Also, the building itself, everything inside of it and the surrounding buildings must be preserved as far as possible. This research analyses, using computer models generated by the softwares Smartfire and buildingEXODUS, a fire situation in a five storeys low-cost buildings. Located in Sao Paulo, the building is a steel cold formed structure. The data used in this work were obtained from architecture, materials and structure, walls and furniture, as well as the occupant data, acquired by the authors from the design and also technical visits. The fire model in this building, based in CFD, was developed in the software SmartFire to simulate the geometry of the edification, the thermal properties of materials, the behavior and fire dynamics compartments fire, with posterior generation of numerical data. These data were inserted in the software buildingEXODUS which, considering the physics and psychological factors of the occupants, and also the data generated in the other software, created a model which simulates the evacuation time of the occupants and their behavior when they face the fire effects The results obtained in the research attested the efficiency of the softwares, which created the simulation of a real fire situation. It was also proved that the building is exempt of the Required Fire Resistance Time. Consequently, it was possible to conclude that the building is adequate concerning to the objectives of saving lives and minimizing material losses by the fire, as a result of the behavior of the building components and the adequate architectural design.